Suaires de papier : Ernest Pignon-Ernest. Interventions et recouvrance - Liliane Louvel (Anglophonia, 2009)
Ernest Pignon-Ernest is a French contemporary artist whose technique consists in printing his (black and white pencils, pen and ink) drawings after great masters (particularly Baroque ones like Caravaggio, but not only) and to stick them up at night on city walls. Thus he left his silkscreen drawings on the walls of Naples, Paris, Soweto, Charleroi, as so many posters meant to shock and make the inhabitants react to some social concern. For his is also a form of committed art; he defended women’s right to abortion, the rights of immigrants, and reinscribed the dead bodies of Les Communards on the stairs of Montmartre. He also "intervened" in Soweto and in Algiers. Cities thus double as necessary backgrounds to the prints. But first and foremost his art is fascinating and his technique absolutely perfect.